2009
DOI: 10.4049/jimmunol.0800126
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I-II Study of α-Galactosylceramide-Pulsed IL-2/GM-CSF-Cultured Peripheral Blood Mononuclear Cells in Patients with Advanced and Recurrent Non-Small Cell Lung Cancer

Abstract: To evaluate the safety, immune responses, and antitumor responses after the administration of α-galactosylceramide (αGalCer) KRN7000-pulsed PBMC cultured with IL-2 and GM-CSF (IL-2/GM-CSF-cultured PBMCs), a phase I-II study in patients with non-small cell lung cancer was conducted. Patients with advanced non-small cell lung cancer or recurrent lung cancer refractory to the standard therapy were eligible. αGalCer-pulsed IL-2/GM-CSF-cultured PBMCs (1 × 109/m2) were i.v. administered four times. Immune responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
171
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 206 publications
(177 citation statements)
references
References 43 publications
4
171
1
1
Order By: Relevance
“…7,15,16,21,30,31 Although clinical trials examining NKT cell activation therapies in patients with advanced/recurrent disease have reported few cases of objective tumor regression, tumors tended to remain stable without the appearance of new metastatic foci. 15,[17][18][19][20]35 This suggests that NKT cell activation therapy might be more effective at targeting metastatic disease than primary tumors. Since primary breast cancer tumors are effectively treated by surgical resection, and disseminated metastasis remains the primary cause of mortality, 50 NKT cell activation therapy presents a promising therapeutic avenue.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…7,15,16,21,30,31 Although clinical trials examining NKT cell activation therapies in patients with advanced/recurrent disease have reported few cases of objective tumor regression, tumors tended to remain stable without the appearance of new metastatic foci. 15,[17][18][19][20]35 This suggests that NKT cell activation therapy might be more effective at targeting metastatic disease than primary tumors. Since primary breast cancer tumors are effectively treated by surgical resection, and disseminated metastasis remains the primary cause of mortality, 50 NKT cell activation therapy presents a promising therapeutic avenue.…”
Section: Discussionmentioning
confidence: 99%
“…We focused on a-GalCer in this study because it has been used extensively in human clinical trials where it has been shown to be safe and well tolerated. 17,18,20 The ability of free a-GalCer to protect from metastasis was transient, suggesting that multiple treatments or higher doses would be needed therapeutically. However, these strategies are limited by the induction of anergy and toxicity, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, based on our previous study of postinfarct heart failure [17], αGC administration may attenuate also LV remodeling and reduce mortality after MI. To date, several clinical trials (Phase I/II) using activated iNKT cells by αGC have been conducted in patients with cancer [45][46][47][48][49]. No severe adverse events were observed in these trials.…”
Section: Clinical Implicationmentioning
confidence: 99%